Food sustainability : diverging implications - Griffith, Chris (British Food Journal., 2004)
The concept of sustainability in general and food sustainability, in particular, entails many aspects and many interpretations. During a conference on food sustainability a broad, multidisciplinary picture was painted and many key issues were dealt with, from ecology, economy and society. In sessions on food security - the focus in developing countries - and food safety - primarily a preoccupation in developed countries - many potential trade-offs and opportunities for regional approaches were identified. The session on governance, therefore, focused on the interaction between multi-level acto.